2014
DOI: 10.1155/2014/350281
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poststroke Health-Related Quality of Life in Nigerian Stroke Survivors: A 1-Year Follow-Up Study

Abstract: This study aims to identify the predictors in the different aspects of the health-related quality of life (HRQoL) and to measure the changes of functional status over time in a cohort of Nigerian stroke survivors. A prospective observational study was conducted in three hospitals of Kano state of Nigeria where stroke survivors receive rehabilitation. The linguistic-validated Hausa versions of the stroke impact scale 3.0, modified Rankin scale, Barthel index and Beck depression inventory scales were used. Paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 39 publications
(32 reference statements)
4
49
0
6
Order By: Relevance
“…In-line with what obtains in other regions of the world, depression was the most important emotional symptom that influences HRQOL of stroke survivors in Africa [2,17,18,20,39,40,29].…”
Section: Relationship Between Emotional Status and Hrqol Of Stroke Susupporting
confidence: 58%
See 3 more Smart Citations
“…In-line with what obtains in other regions of the world, depression was the most important emotional symptom that influences HRQOL of stroke survivors in Africa [2,17,18,20,39,40,29].…”
Section: Relationship Between Emotional Status and Hrqol Of Stroke Susupporting
confidence: 58%
“…In this review severity of stroke related symptoms and impairments were shown to adversely affect HRQOL of African stroke survivors [2,17,22,26,27,28,9]. Importantly the included studies were able to exclude stroke survivors suffering from other life chronic threatening conditions not directly related to stroke that may concurrently impact on their HRQOL of such as cancers [16], brain tumors [13], stroke-like symptom due to previous head injury [13], heart failure [2,29], peritoneal or hemodialysis [2,29] and active psychiatric disease [2].…”
Section: Physical Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…A flow-chart is presented in figure 1. In total, 28 unique studies were included, based on 36 publications [13,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50] that fulfilled all selection criteria. Six studies recruited populations from a rehabilitation setting [18,19,29,34,40],FuPro study [13,38,45,46] and the other studies included hospital-based populations.…”
Section: Resultsmentioning
confidence: 99%